Condições higiênico-sanitárias de restaurantes comerciais do tipo self-service de Belo Horizonte-MG - Carolina Ferreira Rossi (2006)
Hygienic-sanitary conditions of self-service restaurants in Belo Horizonte - MG. A check-list was elaborated to assess compliance with the Good Manufacturing Practices (GMP) in self-service restaurants in Belo Horizonte - MG, from April to July of 2005. Only one out of 30 visited establishments fulfilled more than 75% of the analyzed items. Eight establishments (26,7%) had inspection scores from 50% to 75% while 21 (70%) reached less than 50% of the items listed. Individually, the scores of the analyzed restaurants varied from 28,8% to 80% presenting a median of 44,5%. The handlers, instruments and equipments presented great contamination points, confirmed by microbiological analysis. Samples of sponges, blenders, handling borders and workers hands were collected. In the main part of the samples were found high counts of total coliforms, aerobic mesophilic bacteria and faecal coliforms. There was also observed contamination of some specific microorganisms on the hands of food handlers, where were detected the presence of E. coli (26,9%), Staphylococcus spp (84,6%) and Salmonella spp (30,8%) even after the current hygienic process. The presence of Salmonella spp and E. coli was also verified on the handling boards and in both cases they have reached 11% of the samples. So, the studies showed the hazard of the hygienic-sanitary conditions of those places and the urge of controlling better the stages of food processing.